Sở hữu nhà nước và hành vi chấp nhận rủi ro: Trường hợp các công ty niêm yết Việt Nam - Phùng Đức , Nam (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
By using system GMM estimation method and a panel of Vietnam’s listed firms over the period from 2007 to 2015, this study finds a positive relationship between state ownership and corporate risk taking among these firms. The empirical evidence reveals that state ownership encourages corporate risk taking for increasing returns. The risk-taking behavior exhibited by representatives of state-owned firms may imply that they desire to gain finer reputation, but do not face risk from such behavior. The results re-confirm the important role of corporate governance mechanism in the context of Vietnam.